Effects of Emotional Facial Expression on Time Perception in Patients with Parkinson's Disease. (7th August 2015) - Mioni, Giovanna; Meligrana, Lucia; Grondin, Simon; Perini, Francesco; Bartolomei, Luigi; Stablum, Franca
Abstract: Previous studies have demonstrated that emotional facial expressions alter temporal judgments. Moreover, while some studies conducted with Parkinson's disease (PD) patients suggest dysfunction in the recognition of emotional facial expression, others have shown a dysfunction in time perception. In the present study, we investigate the magnitude of temporal distortions caused by the presentation of emotional facial expressions (anger, shame, and neutral) in PD patients and controls. Twenty-five older adults with PD and 17 healthy older adults took part in the present study. PD patients were divided into two sub-groups, with and without mild cognitive impairment (MCI), based on their neuropsychological performance. Participants were tested with a time bisection task with standard intervals lasting 400 ms and 1600 ms. The effect of facial emotional stimuli on time perception was evident in all participants, yet the effect was greater for PD-MCI patients. Furthermore, PD-MCI patients were more likely to underestimate long and overestimate short temporal intervals than PD-non-MCI patients and controls. Temporal impairment in PD-MCI patients seem to be mainly caused by a memory dysfunction. ( JINS, 2016, 22, 890–899)